The Influence of Work Motivation, Work Environment, and Job Satisfaction on the Performance of Courier Employees at Shopee Express East Semarang Office - Handayani, Lydia Putri; Pradiptya, Adhi; Larasati, Miranda Fuji (Economics and Business Solutions Journal, 2024)
This research aims to ascertain how work motivation, work environment, and job satisfaction affect the performance of courier employees at Kantor Shopee Express Semarang Timur. This research is based on a case study of courier employees at Kantor Shopee Express Semarang Timur. Where there is less than optimal performance of courier employees. The population of this study consisted of all employees of the courier section at the Shopee Express East Semarang Office, with a sample size of 56 respondents. The sampling method used is probability sampling, while the type of probability sampling used is random sampling. The instrument used in this study was a questionnaire and testing with the help of SPSS 24. The findings indicate that (1) work motivation has no impact on courier employees' performance at the Shopee Express in East Semarang Office, (2) The work environment at the Shopee Express East Semarang Office has no impact on the couriers' performance, (3) The performance of courier staff at Shopee Express East Semarang Office is positively and significantly impacted by their job satisfaction